2017
DOI: 10.1016/j.biortech.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different types of anaerobic seed sludge for the high rate anaerobic digestion of pig slurry in UASB reactors

Abstract: Three different types of anaerobic sludge (granular, thickened digestate and anaerobic sewage) were evaluated as seed inoculum sources for the high rate anaerobic digestion of pig slurry in UASB reactors. Granular sludge performance was optimal, allowing a high efficiency process yielding a volumetric methane production rate of 4.1LCHLd at 1.5days HRT (0.248LCHgCOD) at an organic loading rate of 16.4gCODLd. The thickened digestate sludge experimented flotation problems, thus resulting inappropriate for the UAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
(27 reference statements)
3
15
0
5
Order By: Relevance
“…It is known that the presence of inoculum influences the methanogenic activity and can present significant differences for different inoculum sources (Vrieze et al, 2015;Rico et al, 2017). In this study, it is observed that different types of inoculum may also influence the removal of COD and solids.…”
Section: Removal Of Cod (Total and Soluble)mentioning
confidence: 77%
See 1 more Smart Citation
“…It is known that the presence of inoculum influences the methanogenic activity and can present significant differences for different inoculum sources (Vrieze et al, 2015;Rico et al, 2017). In this study, it is observed that different types of inoculum may also influence the removal of COD and solids.…”
Section: Removal Of Cod (Total and Soluble)mentioning
confidence: 77%
“…It is worthy to note that different inocula lead to different biogas production, with significant effect of the inoculum on the Biochemical Methane Potential (BMP) (Vrieze et al, 2015). Another paper (Rico et al, 2017) shows the influences of inocula on the anaerobic digestion of pig slurry in UASB reactor.…”
mentioning
confidence: 99%
“…Rico ve diğ. [12], tarafından yapılan domuz çiftliği atıksularının UASB reaktörde arıtılmasında, uçucu yağ asidi konsantrasyonları 1300-1800 mg/l arasında değişmiştir. Bu değerler bu çalışmada ölçülen VFA konsantrasyonları ile uyumludur.…”
Section: Anaerobik/aerobik Reaktör Sisteminde Ph Ve Vfa Değişimiunclassified
“…Amuda [11], tarafından büyükbaş hayvan çiftliğinden kaynaklanan atıksu karakterizasyonunu belirleme amaçlı yapılan çalışmada KOİ, askıda katı madde (AKM), biyolojik oksijen ihtiyacı (BOİ), TP, toplam kjeldahl azotu (TKN), yağ ve pH parametreleri sırasıyla; 14350 mg/l, 19945 mg/l, 14370 mg/l, 720 mg/l, 280 mg/l, 47 mg/l, 6.7 olarak bulunmuştur. Farklı bir çalışmada ise domuz çiftliği atıksuyunun 3 farklı tür aşı çamuru kullanılarak UASB reaktörlerde arıtımı çalışılmıştır [12]. Kullanılan aşı çamurlarından; biyoetanol üreten tesisin atıksularını arıtan UASB reaktörden alınan granüler aşı çamuru metan oluşum oranı açısından en iyi sonucu vermiştir.…”
Section: Introductionunclassified
“…Rico et al (2017) investigated the effect on granular, thickened digestate and anaerobic sewage which were three types of anaerobic sludge to improve the performance by AD of pig slurry in UASB reactors. The results showed that granular sludge had the best performance which can increase the methane generation rate to 4.1 L CH4 /L · d at 1.5 d HRT and OLR of 16.4 g COD /L ·d.…”
mentioning
confidence: 99%